β-Amyloid Prions and the Pathobiology of Alzheimer’s Disease - Watts, Joel C. (Cold Spring Harb Perspect Med, 2018)
Alzheimer’s disease (AD) is the most common neurodegenerative disease in humans and will pose a considerable challenge to healthcare systems in the coming years. Aggregation of the β-amyloid (Aβ) peptide within the brain is thought to be an initiating event in AD pathogenesis. Many recent studies in transgenic mice have provided evidence that Aβ aggregates become self-propagating during disease, leading to a cascade of protein aggregation in the brain, which may underlie the progressive nature of AD. The ability to self-propagate and the existence of distinct “strains” reveals that Aβ aggregates exhibit many properties indistinguishable from those of prions composed of PrP(Sc) proteins. Here, we review the evidence that Aβ can become a prion during disease and discuss how Aβ prions may be important for understanding the pathobiology of AD.